Environment-friendly sewage treatment flocculant and preparation method thereof

Through the combination of modified micro latex and composite additives, a micro-crosslinked network-like interlaced structure is formed, which solves the problem of insufficient removal effect of existing sewage treatment flocculants on microplastics, phosphorus and heavy metals, and achieves efficient sewage purification and avoids Corrosion of the pipe by flocculant.

CN119285056AActive Publication Date: 2025-01-10HARBIN XINMIAO WATER TREATMENT TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411683350.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-10
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing sewage treatment flocculants have insufficient effect on the removal of microplastics, phosphorus and heavy metals, and iron-based inorganic flocculants are prone to corrode pipeline equipment.

Method used

Using the combination of modified micro latex and composite additives, environmentally friendly sewage treatment flocculants are prepared by reverse phase microemulsion polymerization. The modified micro latex and composite additives form a micro-crosslinked network-like interlaced structure to effectively adsorb and remove the sewage. Greases, microplastics, phosphorus and heavy metals, and avoid corrosion of pipelines by polymerized iron sulfate.

Benefits of technology

It significantly improves the purification effect of sewage treatment, enhances the removal ability of microplastics, phosphorus and heavy metals, and avoids corrosion of the pipeline by flocculants, achieving rapid settlement and efficient capture of pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148899340000101
    Figure BDA0005148899340000101
Patent Text Reader

Abstract

The invention relates to the technical field of flocculants, in particular to an environment-friendly sewage treatment flocculant and a preparation method thereof.The environment-friendly sewage treatment flocculant is prepared from, by weight, 30-35 parts of modified micro latex, 4-6 parts of compound auxiliaries, 2-3 parts of polyferric sulfate, 2-3 parts of activated carbon, 5-10 parts of ethylene glycol and 60-70 parts of water; by adding the modified micro latex and the compound additive, grease, micro plastics, phosphorus and heavy metals in domestic sewage can be effectively removed, meanwhile, due to compounding of the modified micro latex and the compound additive, the purification effect is greatly enhanced, and the problem that an existing flocculating agent is insufficient in removal effect on the micro plastics, the phosphorus and the heavy metals is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flocculants, and in particular to an environmentally friendly sewage treatment flocculant and a preparation method thereof. Background Art

[0002] With the development of cities and the increase in population, the discharge of urban domestic sewage is increasing. Domestic sewage mainly contains substances such as oil, microplastics, phosphorus, and heavy metals. Therefore, domestic sewage needs to be treated. The current commonly used sewage treatment method is to use flocculants to decompose or precipitate chemical substances in sewage, thereby playing a purification role. Most of the commonly used flocculants are iron-based inorganic flocculants, but they are easy to corrode pipeline equipment, thereby affecting water quality. The removal effect of organic polyacrylamide on microplastics, phosphorus and heavy metals can no longer meet market demand. Summary of the invention

[0003] The purpose of the present invention is to provide an environmentally friendly sewage treatment flocculant and a preparation method thereof, which solves the problem that the existing flocculants are insufficient in removing microplastics, phosphorus and heavy metals.

[0004] The purpose of the present invention can be achieved by the following technical scheme: a method for preparing an environmentally friendly sewage treatment flocculant, comprising the following steps: weighing the following raw materials in parts by weight: 30-35 parts of modified micro-latex, 4-6 parts of composite additives, 2-3 parts of polyferric sulfate, 2-3 parts of activated carbon, 5-10 parts of ethylene glycol and 60-70 parts of water, mixing the modified micro-latex, composite additives, polyferric sulfate, activated carbon, ethylene glycol and water to prepare an environmentally friendly sewage treatment flocculant;

[0005] The modified microlatex is prepared by the following steps:

[0006] Step A1: β-cyclodextrin, sodium hydroxide solution and deionized water are mixed, and p-toluenesulfonyl chloride and acetonitrile are added under stirring at a rate of 80-100 rpm and a temperature of 5°C, and the mixture is reacted for 2-3 hours to obtain intermediate 1. Chitosan and acetic acid solution are mixed, and intermediate 1 and N,N-dimethylformamide are added under stirring at a rate of 120-140 rpm and a temperature of 100°C, and the mixture is reacted for 10-12 hours. Maleic anhydride is then added and the mixture is reacted for 3-4 hours to obtain modified chitosan.

[0007] The mass fraction of the sodium hydroxide solution is 10%, and the dosage ratio of β-cyclodextrin, sodium hydroxide solution and p-toluenesulfonyl chloride is 12-14 g: 5-6 mL: 2.5-2.6 g; the volume fraction of the acetic acid solution is 40%, and the dosage ratio of chitosan, acetic acid solution, intermediate 1 and maleic anhydride is 10-12 g: 300-350 mL: 5-6 g: 0.02-0.03 mol;

[0008] During the reaction, under alkaline conditions, the hydroxyl group in β-cyclodextrin reacts with the sulfonic acid chloride in p-toluenesulfonyl chloride to obtain intermediate 1, and intermediate 1 then reacts with the amino group in chitosan to form a secondary amine, thereby grafting β-cyclodextrin onto the chitosan chain, and then maleic anhydride is added to react with the hydroxymethyl group or the unreacted amino group to introduce a double bond to obtain modified chitosan;

[0009] Step A2: liquid paraffin, Span-80, Tween-80 and n-butanol are mixed, stirred at a stirring rate of 800 rpm and a temperature of 50° C. for 30 min to obtain an oil phase, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and deionized water are mixed, stirred at a stirring rate of 300 rpm and a temperature of 30° C., and ammonium persulfate solution is added and stirred for 30 min to obtain an aqueous phase, and the aqueous phase is slowly dripped into the oil phase, reacted at a temperature of 40° C. for 3-4 h, demulsified, and dried to obtain a microemulsion;

[0010] The dosage ratio of liquid paraffin, Span-80, Tween-80 and n-butanol is 7-8g: 2.3-2.5g: 1.5-1.7g: 0.4-0.5g; the mass fraction of ammonium persulfate solution is 1%, and the dosage ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and ammonium persulfate solution is 0.05-0.052mol: 0.01-0.015mol: 0.04-0.05g: 0.8-0.9g: 1-1.2mL;

[0011] In the reaction process, microemulsion is prepared by reverse microemulsion polymerization, using ammonium persulfate as initiator, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide and modified chitosan as monomers;

[0012] The composite auxiliary agent is prepared by the following steps

[0013] Step B1: 4-bromobenzoic acid, ethanol and concentrated sulfuric acid were mixed, and the mixture was reacted for 12 hours at a stirring rate of 120-150 rpm and a temperature of 75°C to obtain intermediate 1. Intermediate 1 was mixed with ether, and the mixture was stirred at a stirring rate of 80-100 rpm and a temperature of 5°C, and n-butyl lithium was added, and the mixture was stirred for 2-3 hours. The mixture was heated to room temperature and trichlorosilane was added, and the mixture was reacted for 12 hours to obtain intermediate 2.

[0014] The mass fraction of concentrated sulfuric acid is 95%, the dosage ratio of 4-bromobenzoic acid, ethanol and concentrated sulfuric acid is 0.1-0.11 mol: 500 mL: 10-11 mL; the dosage ratio of intermediate 1, n-butyl lithium and trichlorosilane is 0.02-0.022 mol: 8-10 mL: 0.005-0.006 mol;

[0015] During the reaction, under the action of concentrated sulfuric acid, the carboxyl group in 4-bromobenzoic acid reacts with ethanol to form an ethyl formate structure to obtain intermediate 1. Then, under the action of n-butyl lithium as an initiator, trichlorosilane is first lithiated and then reacts with intermediate 1 to form a carbon-silicon bond to obtain intermediate 2.

[0016] Step B2: Mix intermediate 2, vinyl ferrocene and tetrahydrofuran, stir at a rate of 120-150 rpm and a temperature of 90°C, add a Custer catalyst, and react for 3-4 hours to obtain intermediate 3; mix intermediate 3, sodium hydroxide and deionized water, stir at a rate of 60-80 rpm and a temperature of 80°C, react for 2-3 hours, cool to room temperature, and add a hydrochloric acid solution to obtain intermediate 4;

[0017] The amount ratio of intermediate 2, vinyl ferrocene and Custer catalyst is 0.05-0.06 mol: 0.07-0.08 mol: 0.8-0.9 g; the mass fraction of hydrochloric acid solution is 35%, and the amount ratio of intermediate 3, sodium hydroxide, deionized water and hydrochloric acid solution is 0.05-0.06 mol: 18-20 g: 400-450 mL: 80-90 mL;

[0018] During the reaction, under the action of Custer's catalyst, the silicon-hydrogen bond in intermediate 2 and the double bond in vinyl ferrocene undergo silicon-hydrogen addition to obtain intermediate 3. The ester group in the ethyl formate structure in intermediate 3 is then broken under the action of sodium hydroxide, and then acidified to form a carboxyl group to obtain intermediate 4.

[0019] Step B3: cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, reacted at a temperature of 120° C. for 3 hours, centrifuged, and filtered to obtain a modified auxiliary agent;

[0020] The ratio of cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide is 0.012 mol: 0.012 mol: 3.5-3.8 g: 30-32 mL;

[0021] During the reaction, a composite additive with a metal organic framework structure was prepared by a solvothermal method using cobalt acetate as a cobalt source and intermediate 4 as a ligand.

[0022] Beneficial effects of the invention: The invention discloses an environmentally friendly sewage treatment flocculant and a preparation method thereof. By adding modified micro-latex and composite additives, it can effectively remove grease, microplastics, phosphorus and heavy metals in domestic sewage. At the same time, due to the compounding between the modified micro-latex and the composite additive, the purification effect is greatly enhanced; during the use of the flocculant, since the modified micro-latex itself is a microsphere structure containing a large amount of cyclodextrin on the surface, and the presence of its cationic sulfonic acid group, the modified micro-latex and the particles in the sewage have charge neutralization and adsorption bridging effects, thereby The particles in the system are destabilized and flocculated, and the composite additive itself is a porous metal organic framework structure. At the same time, because it uses zirconium as the metal element and introduces silicon, it has a good adsorption effect on phosphorus and heavy metal ions, and its structure also avoids the corrosion of pipelines during the use of polyferric sulfate. At the same time, due to the host-guest inclusion complex of the cyclodextrin structure in the modified microlatex and ferrocene in the composite additive, the micro-cross-linked network structure formed not only makes it settle quickly, but also captures more pollutant particles during the sedimentation process, playing a good purification role. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 A method for preparing an environmentally friendly sewage treatment flocculant comprises the following steps: weighing the following raw materials in parts by weight: 30 parts of modified micro-latex, 4 parts of composite additives, 2 parts of commercially available Jiuyue polyferric sulfate, 2 parts of commercially available Jinding activated carbon, 5 parts of ethylene glycol and 60 parts of water, mixing the modified micro-latex, composite additives, polyferric sulfate, activated carbon, ethylene glycol and water to prepare an environmentally friendly sewage treatment flocculant;

[0025] The modified microlatex is prepared by the following steps:

[0026] Step A1: β-cyclodextrin, sodium hydroxide solution and deionized water were mixed, and p-toluenesulfonyl chloride and acetonitrile were added under stirring at a rate of 80 rpm and a temperature of 5°C, and the mixture was reacted for 2 hours to obtain intermediate 1. Commercially available Honghai chitosan and acetic acid solution were mixed, and intermediate 1 and N,N-dimethylformamide were added under stirring at a rate of 120 rpm and a temperature of 100°C, and the mixture was reacted for 10 hours. Maleic anhydride was then added and the mixture was reacted for 3-4 hours to obtain modified chitosan.

[0027] The mass fraction of sodium hydroxide solution is 10%, and the ratio of β-cyclodextrin, sodium hydroxide solution and p-toluenesulfonyl chloride is 12g:5mL:2.5g; the volume fraction of acetic acid solution is 40%, and the ratio of chitosan, acetic acid solution, intermediate 1 and maleic anhydride is 10g:300mL:5g:0.02mol;

[0028] Step A2: Mix commercially available Zhijia liquid paraffin, Span-80, Tween-80 and n-butanol, stir at a stirring rate of 800 rpm and a temperature of 50° C. for 30 min to obtain an oil phase, mix acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and deionized water, stir at a stirring rate of 300 rpm and a temperature of 30° C., add ammonium persulfate solution, stir for 30 min to obtain an aqueous phase, slowly drip the aqueous phase into the oil phase, react at a temperature of 40° C. for 3 h, demulsify, and dry to obtain a microemulsion;

[0029] The amount ratio of liquid paraffin, Span-80, Tween-80 and n-butanol is 7g:2.3g:1.5g:0.4g; the mass fraction of ammonium persulfate solution is 1%, and the amount ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and ammonium persulfate solution is 0.05mol:0.01mol:0.04g:0.8g:1mL;

[0030] The composite auxiliary agent is prepared by the following steps

[0031] Step B1: 4-bromobenzoic acid, ethanol and concentrated sulfuric acid were mixed, and the mixture was reacted for 12 hours at a stirring rate of 120 rpm and a temperature of 75°C to obtain intermediate 1. Intermediate 1 was mixed with ether, and the mixture was stirred at a stirring rate of 80 rpm and a temperature of 5°C, and n-butyl lithium was added, and the mixture was stirred for 2 hours. The mixture was heated to room temperature and trichlorosilane was added, and the mixture was reacted for 12 hours to obtain intermediate 2.

[0032] The mass fraction of concentrated sulfuric acid is 95%, the usage ratio of 4-bromobenzoic acid, ethanol and concentrated sulfuric acid is 0.1 mol: 500 mL: 10 mL; the usage ratio of intermediate 1, n-butyl lithium and trichlorosilane is 0.02 mol: 8 mL: 0.005 mol;

[0033] Step B2: Mix intermediate 2, vinyl ferrocene and tetrahydrofuran, stir at a rate of 120 rpm and a temperature of 90°C, add a Custer catalyst, and react for 3 hours to obtain intermediate 3; mix intermediate 3, sodium hydroxide and deionized water, stir at a rate of 60 rpm and a temperature of 80°C, react for 2 hours, cool to room temperature, and add a hydrochloric acid solution to obtain intermediate 4;

[0034] The amount ratio of intermediate 2, vinyl ferrocene and Custer catalyst is 0.05 mol: 0.07 mol: 0.8 g; the mass fraction of hydrochloric acid solution is 35%, and the amount ratio of intermediate 3, sodium hydroxide, deionized water and hydrochloric acid solution is 0.05 mol: 18 g: 400 mL: 80 mL;

[0035] Step B3: cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, reacted at a temperature of 120° C. for 3 hours, centrifuged, and filtered to obtain a modified auxiliary agent;

[0036] The usage ratio of cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide is 0.012 mol: 0.012 mol: 3.5 g: 30 mL.

[0037] Example 2 A method for preparing an environmentally friendly sewage treatment flocculant comprises the following steps: weighing the following raw materials in parts by weight: 30 parts of modified micro-latex, 6 parts of composite additives, 3 parts of commercially available Jiuyue polyferric sulfate, 3 parts of commercially available Jinding activated carbon, 10 parts of ethylene glycol and 70 parts of water, mixing the modified micro-latex, composite additives, polyferric sulfate, activated carbon, ethylene glycol and water to prepare an environmentally friendly sewage treatment flocculant;

[0038] The modified microlatex is prepared by the following steps:

[0039] Step A1: β-cyclodextrin, sodium hydroxide solution and deionized water were mixed, and p-toluenesulfonyl chloride and acetonitrile were added under stirring at a rate of 100 rpm and a temperature of 5°C, and the mixture was reacted for 3 hours to obtain intermediate 1. Commercially available Honghai chitosan and acetic acid solution were mixed, and intermediate 1 and N,N-dimethylformamide were added under stirring at a rate of 120 rpm and a temperature of 100°C, and the mixture was reacted for 12 hours. Maleic anhydride was then added and the mixture was reacted for 3-4 hours to obtain modified chitosan.

[0040] The mass fraction of sodium hydroxide solution is 10%, and the ratio of β-cyclodextrin, sodium hydroxide solution and p-toluenesulfonyl chloride is 14g:5mL:2.5g; the volume fraction of acetic acid solution is 40%, and the ratio of chitosan, acetic acid solution, intermediate 1 and maleic anhydride is 12g:300mL:5g:0.03mol;

[0041] Step A2: Mix commercially available Zhijia liquid paraffin, Span-80, Tween-80 and n-butanol, stir at a stirring rate of 800 rpm and a temperature of 50° C. for 30 min to obtain an oil phase, mix acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and deionized water, stir at a stirring rate of 300 rpm and a temperature of 30° C., add ammonium persulfate solution, stir for 30 min to obtain an aqueous phase, slowly drip the aqueous phase into the oil phase, react at a temperature of 40° C. for 3-4 h, demulsify, and dry to obtain a microemulsion;

[0042] The amount ratio of liquid paraffin, Span-80, Tween-80 and n-butanol is 8g:2.3g:1.7g:0.4g; the mass fraction of ammonium persulfate solution is 1%, and the amount ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and ammonium persulfate solution is 0.052mol:0.01mol:0.05g:0.8g:1.2mL;

[0043] The composite auxiliary agent is prepared by the following steps

[0044] Step B1: 4-bromobenzoic acid, ethanol and concentrated sulfuric acid were mixed, and the mixture was reacted for 12 hours at a stirring rate of 150 rpm and a temperature of 75°C to obtain intermediate 1. Intermediate 1 was mixed with ether, and the mixture was stirred at a stirring rate of 80 rpm and a temperature of 5°C, and n-butyl lithium was added, and the mixture was stirred for 3 hours. The mixture was heated to room temperature and trichlorosilane was added, and the mixture was reacted for 12 hours to obtain intermediate 2.

[0045] The mass fraction of concentrated sulfuric acid is 95%, the usage ratio of 4-bromobenzoic acid, ethanol and concentrated sulfuric acid is 0.11 mol: 500 mL: 10 mL; the usage ratio of intermediate 1, n-butyl lithium and trichlorosilane is 0.02 mol: 10 mL: 0.005 mol;

[0046] Step B2: Mix intermediate 2, vinyl ferrocene and tetrahydrofuran, stir at a stirring rate of 120 rpm and a temperature of 90°C, add a Custer catalyst, and react for 4 hours to obtain intermediate 3; mix intermediate 3, sodium hydroxide and deionized water, stir at a stirring rate of 80 rpm and a temperature of 80°C, react for 2 hours, cool to room temperature, and add a hydrochloric acid solution to obtain intermediate 4;

[0047] The amount ratio of intermediate 2, vinyl ferrocene and Custer catalyst is 0.06 mol: 0.07 mol: 0.9 g; the mass fraction of hydrochloric acid solution is 35%, and the amount ratio of intermediate 3, sodium hydroxide, deionized water and hydrochloric acid solution is 0.06 mol: 18 g: 450 mL: 80 mL;

[0048] Step B3: cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, reacted at a temperature of 120° C. for 3 hours, centrifuged, and filtered to obtain a modified auxiliary agent;

[0049] The usage ratio of cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide is 0.012 mol: 0.012 mol: 3.5 g: 32 mL.

[0050] Example 3 A method for preparing an environmentally friendly sewage treatment flocculant, comprising the following steps: weighing the following raw materials in parts by weight: 35 parts of modified micro-latex, 6 parts of composite additives, 3 parts of commercially available Jiuyue polyferric sulfate, 3 parts of commercially available Jinding activated carbon, 10 parts of ethylene glycol and 70 parts of water, mixing the modified micro-latex, composite additives, polyferric sulfate, activated carbon, ethylene glycol and water to prepare an environmentally friendly sewage treatment flocculant;

[0051] The modified microlatex is prepared by the following steps:

[0052] Step A1: β-cyclodextrin, sodium hydroxide solution and deionized water were mixed, and p-toluenesulfonyl chloride and acetonitrile were added under stirring at a rate of 100 rpm and a temperature of 5°C, and the mixture was reacted for 3 hours to obtain intermediate 1. Commercially available Honghai chitosan and acetic acid solution were mixed, and intermediate 1 and N,N-dimethylformamide were added under stirring at a rate of 140 rpm and a temperature of 100°C, and the mixture was reacted for 12 hours. Maleic anhydride was then added and the mixture was reacted for 4 hours to obtain modified chitosan.

[0053] The mass fraction of sodium hydroxide solution is 10%, and the ratio of β-cyclodextrin, sodium hydroxide solution and p-toluenesulfonyl chloride is 14g:6mL:2.6g; the volume fraction of acetic acid solution is 40%, and the ratio of chitosan, acetic acid solution, intermediate 1 and maleic anhydride is 12g:350mL:6g:0.03mol;

[0054] Step A2: Mix commercially available Zhijia liquid paraffin, Span-80, Tween-80 and n-butanol, stir for 30 min at a stirring rate of 800 rpm and a temperature of 50° C. to obtain an oil phase, mix acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and deionized water, stir at a stirring rate of 300 rpm and a temperature of 30° C., add ammonium persulfate solution, stir for 30 min, to obtain an aqueous phase, slowly drip the aqueous phase into the oil phase, react at a temperature of 40° C. for 4 h, demulsify, and dry to obtain a microemulsion;

[0055] The amount ratio of liquid paraffin, Span-80, Tween-80 and n-butanol is 8g:2.5g:1.5-1.7g:0.5g; the mass fraction of ammonium persulfate solution is 1%, and the amount ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and ammonium persulfate solution is 0.052mol:0.015mol:0.05g:0.9g:1.2mL;

[0056] The composite auxiliary agent is prepared by the following steps

[0057] Step B1: 4-bromobenzoic acid, ethanol and concentrated sulfuric acid were mixed, and the mixture was reacted for 12 hours at a stirring rate of 150 rpm and a temperature of 75°C to obtain intermediate 1. Intermediate 1 was mixed with ether, and the mixture was stirred at a stirring rate of 100 rpm and a temperature of 5°C, and n-butyl lithium was added, and the mixture was stirred for 3 hours. The mixture was heated to room temperature and trichlorosilane was added, and the mixture was reacted for 12 hours to obtain intermediate 2.

[0058] The mass fraction of concentrated sulfuric acid is 95%, the usage ratio of 4-bromobenzoic acid, ethanol and concentrated sulfuric acid is 0.11 mol: 500 mL: 11 mL; the usage ratio of intermediate 1, n-butyl lithium and trichlorosilane is 0.022 mol: 10 mL: 0.006 mol;

[0059] Step B2: Mix intermediate 2, vinyl ferrocene and tetrahydrofuran, stir at a rate of 150 rpm and a temperature of 90°C, add a Custer catalyst, and react for 3-4 hours to obtain intermediate 3; mix intermediate 3, sodium hydroxide and deionized water, stir at a rate of 80 rpm and a temperature of 80°C, react for 3 hours, cool to room temperature, and add a hydrochloric acid solution to obtain intermediate 4;

[0060] The amount ratio of intermediate 2, vinyl ferrocene and Custer catalyst is 0.06 mol: 0.08 mol: 0.9 g; the mass fraction of hydrochloric acid solution is 35%, and the amount ratio of intermediate 3, sodium hydroxide, deionized water and hydrochloric acid solution is 0.06 mol: 20 g: 450 mL: 90 mL;

[0061] Step B3: cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, reacted at a temperature of 120° C. for 3 hours, centrifuged, and filtered to obtain a modified auxiliary agent;

[0062] The usage ratio of cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide is 0.012 mol: 0.012 mol: 3.8 g: 32 mL.

[0063] Comparative Example 1 Compared with Example 3, this comparative example removes the intermediate 1 in the preparation process of the modified microlatex in Example 3, and the other steps are the same.

[0064] Comparative Example 2 Compared with Example 3, this comparative example removes 2-acrylamide-2-methylpropanesulfonic acid in the preparation process of the modified microlatex in Example 3, and the other steps are the same.

[0065] Comparative Example 3 Compared with Example 3, this comparative example replaces the composite auxiliary agent in the preparation process of the environmentally friendly sewage treatment flocculant in Example 3 with commercially available ZIF-8 material, and the other steps are the same.

[0066] Take the environmentally friendly sewage treatment flocculants prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, refer to GB 11914-89, measure their chemical oxygen demand, refer to GB 13200-91 and use kaolin to simulate wastewater, test the turbidity of the supernatant after flocculation, prepare 50 mg / L copper ion solution, measure the ion concentration after adsorption, and calculate the removal efficiency. Use 0.1 mg / L hydrochloric acid and sodium hydroxide solution as elution and regeneration solution, and calculate its performance retention rate after four adsorption-desorption. The test results are as follows:

[0067]

[0068] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, Comparative Example 1 is compared with Example 3, in which the intermediate 1 in the preparation process of the modified microlatex in Example 3 is removed, and its performance is greatly reduced due to the lack of cyclodextrin structure. In Comparative Example 2, 2-acrylamide-2-methylpropane sulfonic acid in the preparation process of the modified microlatex in Example 3 is removed, and its performance is greatly reduced due to the lack of cationic groups. In Comparative Example 3, the composite auxiliary agent in the preparation process of the environmentally friendly sewage treatment flocculant in Example 3 is replaced with a commercially available ZIF-8 material. Since the ZIF-8 material cannot form a micro-cross-linked network structure with the modified microlatex, its performance is greatly reduced.

[0069] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an environmentally friendly sewage treatment flocculant, characterized in that: The method comprises the following steps: weighing the following raw materials in parts by weight: 30-35 parts of modified micro-latex, 4-6 parts of composite auxiliary agent, 2-3 parts of polyferric sulfate, 2-3 parts of activated carbon, 5-10 parts of ethylene glycol and 60-70 parts of water, and mixing the modified micro-latex, composite auxiliary agent, polyferric sulfate, activated carbon, ethylene glycol and water to prepare an environmentally friendly sewage treatment flocculant.

2. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 1, characterized in that: The modified microlatex is prepared by the following steps: Step A1: β-cyclodextrin, sodium hydroxide solution and deionized water are mixed, and p-toluenesulfonyl chloride and acetonitrile are added under stirring at a rate of 80-100 rpm and a temperature of 5°C, and the mixture is reacted for 2-3 hours to obtain intermediate 1. Chitosan and acetic acid solution are mixed, and intermediate 1 and N,N-dimethylformamide are added under stirring at a rate of 120-140 rpm and a temperature of 100°C, and the mixture is reacted for 10-12 hours. Maleic anhydride is then added and the mixture is reacted for 3-4 hours to obtain modified chitosan. Step A2: Liquid paraffin, Span-80, Tween-80 and n-butanol are mixed, and stirred for 30 minutes at a stirring rate of 800 rpm and a temperature of 50° C. to obtain an oil phase; acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and deionized water are mixed, and stirred at a stirring rate of 300 rpm and a temperature of 30° C., and ammonium persulfate solution is added and stirred for 30 minutes to obtain an aqueous phase; the aqueous phase is slowly dripped into the oil phase, and the reaction is carried out at a temperature of 40° C. for 3-4 hours, demulsified, and dried to obtain a microemulsion.

3. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 2, characterized in that: In step A1: the mass fraction of the sodium hydroxide solution is 10%, and the amount ratio of β-cyclodextrin, sodium hydroxide solution and p-toluenesulfonyl chloride is 12-14 g: 5-6 mL: 2.5-2.6 g; the volume fraction of the acetic acid solution is 40%, and the amount ratio of chitosan, acetic acid solution, intermediate 1 and maleic anhydride is 10-12 g: 300-350 mL: 5-6 g: 0.02-0.03 mol.

4. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 2, characterized in that: In step A2: the ratio of liquid paraffin, Span-80, Tween-80 and n-butanol is 7-8 g: 2.3-2.5g:1.5-1.7g:0.4-0.5g; the mass fraction of the ammonium persulfate solution is 1%, and the dosage ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, N,N-methylenebisacrylamide, modified chitosan and ammonium persulfate solution is 0.05-0.052mol:0.01-0.015mol:0.04-0.05g:0.8-0.9g:1-1.2mL.

5. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 1, characterized in that: The composite auxiliary agent is prepared by the following steps Step B1: 4-bromobenzoic acid, ethanol and concentrated sulfuric acid were mixed, and the mixture was reacted for 12 hours at a stirring rate of 120-150 rpm and a temperature of 75°C to obtain intermediate 1. Intermediate 1 was mixed with ether, and the mixture was stirred at a stirring rate of 80-100 rpm and a temperature of 5°C, and n-butyl lithium was added, and the mixture was stirred for 2-3 hours. The mixture was heated to room temperature and trichlorosilane was added, and the mixture was reacted for 12 hours to obtain intermediate 2. Step B2: Mix intermediate 2, vinyl ferrocene and tetrahydrofuran, stir at a rate of 120-150 rpm and a temperature of 90°C, add a Custer catalyst, and react for 3-4 hours to obtain intermediate 3; mix intermediate 3, sodium hydroxide and deionized water, stir at a rate of 60-80 rpm and a temperature of 80°C, react for 2-3 hours, cool to room temperature, and add a hydrochloric acid solution to obtain intermediate 4; Step B3: Cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide are mixed, ultrasonically dispersed for 20 minutes, reacted at a temperature of 120° C. for 3 hours, centrifuged, filtered, and a modified auxiliary agent is obtained.

6. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 5, characterized in that: In step B1, the mass fraction of concentrated sulfuric acid is 95%, the usage ratio of 4-bromobenzoic acid, ethanol and concentrated sulfuric acid is 0.1-0.11 mol: 500 mL: 10-11 mL; the usage ratio of intermediate 1, n-butyl lithium and trichlorosilane is 0.02-0.022 mol: 8-10 mL: 0.005-0.006 mol.

7. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 5, characterized in that: In step B2: the amount ratio of intermediate 2, vinyl ferrocene and Custer catalyst is 0.05-0.06 mol: 0.07-0.08 mol: 0.8-0.9 g; the mass fraction of hydrochloric acid solution is 35%, and the amount ratio of intermediate 3, sodium hydroxide, deionized water and hydrochloric acid solution is 0.05-0.06 mol: 18-20 g: 400-450 mL: 80-90 mL.

8. The method for preparing an environmentally friendly sewage treatment flocculant according to claim 5, characterized in that: In step B3, the ratio of cobalt acetate, intermediate 4, polyvinyl pyrrolidone and N,N-dimethylformamide is 0.012 mol: 0.012 mol: 3.5-3.8 g: 30-32 mL.

9. An environmentally friendly sewage treatment flocculant, characterized in that: Prepared according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-molecular chitosan composite flocculant

    CN106673165A

  • Composite high-molecular sewage treatment flocculant and preparation method thereof

    CN110526363A

  • Preparation method and application of modified chitosan microsphere double-container corrosion inhibitor

    CN118725355A